2017
DOI: 10.1177/0959683617735590
|View full text |Cite
|
Sign up to set email alerts
|

Land use, settlement, and plant diversity in Iron Age Northwest France

Abstract: Various studies using pollen stratigraphies have demonstrated significant correlations between Holocene plant diversity, climate, and human activities. Studies that have analyzed longer Holocene timescales tend to discuss cultural data very superficially. This is remarkable because detailed insights into past human activities may be key to gain an understanding of the observed trends in biodiversity. This study aims to reconstruct and explain spatio-temporal trends in past plant diversity (alpha, temporal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…10c). This palynological trend confirms the major human-induced landscape transformation that occurred under enhanced agro-pastoral activities discussed with archeological (Pailler and Nicolas, 2019) and continental palynological (Marguerie, 1990(Marguerie, , 1992(Marguerie, , 1993Gaudin, 2004;van Beek et al, 2018) data. In Guidel, a second major shift in terms of human impact, highlighted by the sharp drop of arboreal taxa and the related increase of Poaceae percentages (Fig.…”
Section: The Anthropogenic Pollen Signature Along the South Brittany ...supporting
confidence: 74%
See 1 more Smart Citation
“…10c). This palynological trend confirms the major human-induced landscape transformation that occurred under enhanced agro-pastoral activities discussed with archeological (Pailler and Nicolas, 2019) and continental palynological (Marguerie, 1990(Marguerie, , 1992(Marguerie, , 1993Gaudin, 2004;van Beek et al, 2018) data. In Guidel, a second major shift in terms of human impact, highlighted by the sharp drop of arboreal taxa and the related increase of Poaceae percentages (Fig.…”
Section: The Anthropogenic Pollen Signature Along the South Brittany ...supporting
confidence: 74%
“…These API increases are also observed in core MD08-3204 CQ, except for the 6.4-5.1 ka BP interval that corresponds to a Mid-Holocene period when we argue for a less continental influence and therefore a lower API transmission to the platform (subsection 5.3.2.). General intensification of anthropogenic activities during these three intervals was not recorded in previous continental studies (Visset et al, 1995(Visset et al, , 1996Gaudin, 2004;Visset and Bernard, 2006;van Beek et al, 2018). Regarding core CBT-CS11, the API signal seems to show an opposite behavior, although the anthropogenic history of the Loire watersheds is not opposite to that of the South Brittany ones.…”
Section: Impact Of Multi-secular Hydro-climatic Forcing On the Anthro...mentioning
confidence: 48%
“…On the other hand, positive correlation between vegetation diversity (i.e. richness) and human activities were revealed as well (Paillet et al, 2010; van Beek et al, 2018), under the condition of so-called intermediate disturbance (Wilkinson, 1999). The record from Beihai Wetland revealed that the driving forces of regional vegetation diversity shifted from natural factors to human induced impacts.…”
Section: Discussionmentioning
confidence: 99%